Determinants of Achievement of Basic Immunization in Puskesmas Cot Seumeureung, Aceh Barat - Muhammad Husaini; Anasril Anasril; Tri Mulyono Herlambang; Maryono Maryono (Universitas Teuku Umar, 2021)
Basic Immunization Achievement data at Puskesmas Cot Seumeureung is 58.9% with 256 babies. Based on interviews with 2 mothers, the most common problem found in terms of immunization is that mothers are afraid to give immunizations because their babies will have a fever so that their husbands will be angry or in other words, their husbands will not allow them. The purpose of this study was to determine the determinants of basic immunization attainment in the working area of the Cot Seumeureung, Aceh Barat. This type of research is cross sectional, the research was conducted from 30 July to 10 August 2019. With a population of 256 mothers, the sample was taken using purposive sampling technique. Data collection was carried out by distributing questionnaires, univariate and bivariate data analysis. The results of this study indicate that there is an influence of attitudes on the achievement of basic immunization with p value = 0.005 (α = 0.05) and the influence of family support on the achievement of basic immunization with a value of p value = 0.014 (α = 0.05) and there is no effect on the affordability of immunization services towards the achievement of basic immunization with p value = 0.291 (α = 0.05). It is suggested to mothers and families who have babies to be able to increase knowledge about immunization so that the family increases support so that the basic immunization outcomes can be improved again.